Theoretical analysis of the reactivity of chloroquine and hydroxychloroquine - Omer, Rebaz Anwar; Ahmed, Lana O.; Koparir, Matin; Koparir, Pelin (Natl Inst Science Communication-Niscair, 2020)
Chloroquine (CQ) and Hydroxychloroquine (HCQ) have a low safety margin and its toxic effects are closely related to the ingested dose. Both drugs were tested for reactivity under different conditions but still need to be understood. A thermodynamic and kinetic study with control the electronic properties also show the reaction of the molecule. In this study, theoretical calculations have been performed using Density Functional Theory (DFT) and Hartree-Fock (HF) to find the band gap energy and determine a suitable basis set. A computation based on B3LYP level was accomplished to obtain the geometrical structures for both CQ and HCQ molecules. Based on the B3LYP/6-31G(d,p) basis set, DFT measurements of frontier molecular orbitals and molecular electrostatic potentials have been implemented for both CQ and HCQ. The atomic charge distribution of nitrogen and oxygen is calculated for CQ and HCQ using DFT and HF on a basis set 6-31G**. Ab initio DFT with HF at 6-31G** basis set is performed for thermodynamic analysis for both CQ and HCQ structures.
Keywords: Chloroquine; Density Functional Theory (DFT); ESP; MOMO-LUMO; Hydroxychloroquine; Hartree-Fock (HF)